PENGARUH STRES KERJA DAN IKLIM ORGANISASI TERHADAP TURNOVER INTENTION - Sapulette, Ludy (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2017)
This study aims to analyze the influence of work stress and organizational climate on job satisfaction and employee turnover intention. Research data collected through questionnaires distributed to employees of PT Bank Mandiri Ambon Branch, processed using SPSS 21 and analyzed by path analysis. The result of the analysis showed that job stress had a negative effect on job satisfaction and positive significant to turnover intention. Furthermore, organizational climate has positive and significant effect on job satisfaction, and negatively on employee intention turnover. Similarly, job satisfaction negatively affect employee intent turnover. From the results of this study, can provide input for the Bank Mandiri in Ambon, in order for employees to feel satisfied in working and no or less turnover intention, it is necessary to create a conducive organizational climate and efforts to eliminate the factors that cause work stress is an important thing to always be considered. Can be done through the refreshing program, family gathering and sports together are regularly done by the management.